Impact of using genotyping to predict SERF negative phenotype in Thai blood donor populations - Oytip Nathalang (2020)
© 2020 Korean Society of Hematology Background SERF(+) is a high prevalence antigen in the Cromer blood group system that is encoded by a CROM*01.12 allele. The SERF(-) on red cells is caused by a single nucleotide variation, c.647C＞T, in exon 5 of the Decay-accelerating factor, DAF gene. Alloanti-SERF was found in a pregnant Thai woman, and a SERF(-) individual was found among Thai blood donors. Since anti-SERF is commercially unavailable, this study aimed to develop appropriate genotyping methods for CROM*01.12 and CROM*01.-12 alleles and predict the SERF(-) phenotype in Thai blood donors. Methods DNA samples obtained from 1,580 central, 300 northern, and 427 southern Thai blood donors were genotyped for CROM*01.12 and CROM*01.-12 allele detection using in-house PCR with sequence-specific primer (PCR-SSP) confirmed by DNA sequencing. Results Validity of the PCR-SSP genotyping results agreed with DNA sequencing; CROM*01.12/ CROM*01.12 was the most common (98.42%, 98.00%, and 98.59%), followed by CROM*01.12/CROM*01.-12 (1.58%, 2.00%, and 1.41%) among central, northern, and southern Thais, respectively. CROM*01.-12/CROM*01.-12 was not detected in all three populations. The alleles found in central Thais did not significantly differ from those found in northern and southern Thais. Conclusion This study is the first to distinguish the predicted SERF phenotypes from genotyping results obtained using in-house PCR-SSP, confirming that the CROM*01.-12 allele frequency ranged from 0.007 to 0.010 in three Thai populations. This helps identify the SERF(-) phenotype among donors and patients, ultimately preventing adverse transfusion reactions.